AUTOPLAGIARISM AND SCIENTIFIC RESEARCH ACTIVITY - Cristian Răzvan CERCEL (Challenges of the Knowledge Society, 2019)
Writing a PhD thesis involves a long and profound scientific research activity. In this context of research, a number of incident factors may lead to the elaboration of a PhD thesis that is original or not. Some of these factors would be plagiarism and autoplagiarism. This paper aims to highlight the issue of plagiarism and autoplagiarism in the context of scientific research activity, while at the same time reaching some essential points regarding the intellectual property right. Last but not least, this paper aims to present some issues related to the current regulation of plagiarism and autoplagiarism, through legal provisions aimed at ensuring good conduct in the scientific research and development activity, but also their relations with the rules on the protection of intellectual property rights.